Age-appropriate communication with children and young people in the healthcare system - Line Klingen Gjærde; Jakob Thestrup; Jane Hybschmann; Barbara Esbjørn; Daniel Dybdal; Karen Barslund Kjeldsen; Julie Høgh; Lisbeth Gath; Jannie Haaber; Morten Schrøder; Pernille Opstrup; Søren Walther-Larsen; et al. (Ugeskrift for Læger, 2026)
Involving children and adolescents in their own treatment and care is a right according to the UN Convention on the Rights of the Child, and a central aspect of child- and youth-centered care. Yet, many pediatric patients feel overlooked in communication with healthcare professionals. This review presents an interprofessional pediatric communication model that supports communicative competences and relational skills throughout the patient encounter to promote trust, understanding, and collaboration with children, adolescents, and their parents.